Economics without time : a science blind to the forces of historical change - Snooks, Graeme Donald (Basingstoke : Macmillan; Ann Arbor : University of Michigan Press, 1993)
This is a book about real time in economics, a dimension increasingly unused by the leading edge of the profession. This, it is argued, has serious implications for economics role as the premier policy-advising source for national governments and international organisations.
Includes bibliographical references (p. 302-319) and index.
oif 24/04/15
Loan
Keywords: Economics -- Methodology; Economic history; Europe -- Economic conditions